Digital marketing development strategy of rama cassava chips at tajur halang village - Abel Gandhy; Mutia Raras Respati; Haqi Fadillah; Aries Maesya; Adi Surya Panji Gumilang (Institute of Computer Science (IOCS), 2026)
This study aims to formulate appropriate digital marketing strategies to increase brand awareness and sales for the Rama Cassava Chips SME amid increasingly competitive market dynamics. Unfortunately, Rama Cassava Chips has not yet implemented digital marketing and still relies on distributors, resulting in declining sales. The implementation of digital marketing strategies is essential given the behavior of the target market Millennials and Generation Z who are known as digital natives. Unfortunately, previous research has not specifically addressed digital marketing strategies suitable for the subject’s circumstances. This is a descriptive study utilizing the IFE, EFE, IE Matrix, and SWOT Matrix as analytical tools. The analysis results show that an IFE score of 3.15 and an EFE score of 2.30 place the business in the grow and build position. This indicates that the business possesses strong internal strengths but faces significant external pressures. The recommended strategic alternatives include strengthening digital branding through storytelling, developing an omnichannel marketing system, enhancing brand identity, pursuing product differentiation, and leveraging digital data. The findings of this study theoretically contribute to research in the field of digital marketing, particularly in the context of agro-industrial SMEs producing local products such as cassava chips, and practically provide guidance for SMEs, specifically Rama Cassava Chips in designing more targeted digital marketing strategies.